Crustal structure beneath southern Norway imaged by magnetotellurics - Cherevatova, M.; Smirnov, Maxim Yu; Korja, Toivo; Kaikkonen, Pertti; Pedersen, Laust B.; Hübert, Juliane; Kamm, Jochen; Kalscheuer, Thomas (Tectonophysics, 2014)
ISSN:0040-1951 ISSN:1879-3266